P–V–T–X evolution of olivine-hosted melt inclusions during high-temperature homogenization treatment. (1st January 2016) - Schiavi, Federica; Provost, Ariel; Schiano, Pierre; Cluzel, Nicolas
Abstract: During low–high temperature ( T ) cycles imposed on olivine-hosted melt inclusions (MIs) we observe a systematic increase in homogenization temperature ( T h ) with time, regardless of their initial major-element and H2 O contents. Bubble persistence at high T suggests that inclusion internal pressure ( P int ) is lower than its original, trapping pressure. We explore how reversible and irreversible processes modify the composition ( X ), volume ( V ) and P int of heated MIs, and compare the results of theoretical modeling with experimental observations of MIs from FAMOUS Zone (FZ, Mid-Atlantic Ridge) and La Sommata (SOM, Vulcano, Aeolian Islands) basaltic samples. Due to olivine dissolution at inclusion walls and thermoelastic deformation, P int – V – X conditions change significantly upon heating. Olivine dissolution induces changes in major-element composition (i.e., enrichment in Fe and Mg), morphology and volume (up to +25% at 1500 °C). We provide equations for the thermoelastic deformation of olivine bearing a two-phase, liquid–gas inclusion for the end-member cases of chemical equilibrium and no exchange between gas and liquid. These equations allow P int – V evolution to be related to variations in bubble volume fraction. Upon heating, both P int and V variations are smaller in the presence of a gas bubble than for a homogeneous liquid inclusion, at the same T . Dissolution–reprecipitation and thermoelastic deformation of the olivine host are reversible processes, so initial P int – V – X conditions are restored upon cooling. On the contrary, water loss from MIs and plastic deformation of the olivine host are processes that irreversibly lower P int, and account for the systematic increase of T h with time. Our theoretical and experimental investigations suggest that the increase of T h in volatile-rich SOM MIs is mainly related to progressive release of water. Compared to larger MIs located at a similar distance from the olivine rim, smaller MIs show a faster increase in T h with time, consistent with the effects of diffusive water loss. Nonetheless, we cannot exclude the combined effect of incipient plastic deformation, which would enhance water loss by diffusion along dislocations. The increase in T h in volatile-poor FZ MIs is driven mainly by elasto-plastic deformation of the olivine host, which becomes more marked with increasing T and decreased distance from MI wall to olivine rim. Occurrence of plastic deformation in FZ olivines is testified by dislocation patterns observed around inclusions. In general, conducting homogenization experiments at 1 atm prevents MI homogenization happening at a T h equal to entrapment T . This is due to a drop in P int caused by the elastic deformation that affects olivine phenocrysts bearing pressurized MIs during magma ascent. Predicted increase in T h ranges from a few degrees to tens of degrees depending on entrapment conditions, melt composition and volatile contents.